Information acquisition and welfare - Luca Colombo; Gianluca Femminis; Alessandro Pavan (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 2012)
We study information acquisition in a flexible framework with strategic complementarity or substitutability in actions and a rich set of externalities that are responsible for possible wedges between the equilibrium and the efficient acquisition of information. First, we relate the (in)efficiency in the acquisition of information to the (in)efficiency in the use of information and explain why efficiency in the use does not guarantee efficiency in the acquisition. Next, we show how the acquisition of private information affects the social value of public information (i.e., the comparative statics of equilibrium welfare with respect to the quality of public information). Finally, we illustrate the implications of our results in a few applications that include beauty contests, monetary economies with price-setting complementarities, and economies with negative production externalities.
Keywords: C72; D62; D83; E50; 330; endogenous information; strategic complementarity / substitutability; externalities; efficiency; welfare; endogenous information; strategic complementarity/substitutability; externalities; efficiency; welfare